Pelaksanaan Fungsi Pengawasan Badan Permusyarawatan Desa (BPD) dalam Penyelenggaraan Pemerintahan Desa (Studi Pada Desa Tabore Kecamatan Mantangai Kabupaten Kapuas) - Yoga; Jaya, Imanuel; Bertho, Edward Melio (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
The implementation of the supervisory function by the Village Consultative Body (BPD) plays a crucial role in supporting the creation of transparent, accountable, and participatory village governance. BPD functions as a representative institution of the village community that oversees the administration of government, including the management of village finances and the implementation of public policies at the village level. However, in practice, various challenges still hinder the optimal execution of this function. This study aims to examine in depth the implementation of the supervisory function of BPD in Tabore Village, Mantangai Subdistrict, Kapuas Regency. The study uses a qualitative approach with a descriptive case study method. Data were collected through observation, in-depth interviews, documentation, and literature review. The research informants consist of village government officials, BPD members, and community leaders. Data analysis was conducted using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing/verification. The results show that the BPD of Tabore Village has carried out its supervisory functions in accordance with the theory of Juliantara (2005) as cited in Ngga (2022), which includes: (1) supervision of the implementation of Village Regulations, (2) supervision of the Village Revenue and Expenditure Budget (APBDes), and (3) supervision of decisions made by the Village Head. These three aspects have been implemented effectively by the BPD, which also actively involves the community in village deliberations as a form of transparency and public accountability. Nevertheless, the effectiveness of supervision still needs to be improved, particularly through institutional capacity building, enhancing the quality of community participation, and strengthening the synergy between BPD and the Village Government to achieve optimal and responsive village governance.